Currencies analysis based on stability using apriori-algorithm - ULLAH KHAN, Hameed; ULLAH, Zahid; MAHMUD, Maqsood (Annals of Spiru Haret University. Economic Series, 2010)
This paper presents the stability of currency that is more stable with respect to other currencies. Various currencies are studied and graphs are plotted with reference to dates on a yearly basis and analyze its patterns. The stability of a currency was determined by using Apriori-algorithm. This algorithm maneuver in continues manner unless the desired results are achieved.